Prevalence and Factors Associated With Surgical Site Infections in the University Clinics of Traumatology and Urology of the National University Hospital Centre Hubert Koutoukou Maga in Cotonou - Dégbey, Cyriaque; Kpozehouen, Alphonse; Coulibaly, Drissa; Chigblo, Pascal; Avakoudjo, Josué; Ouendo, Edgard-Marius; Hans-Moevi, Aristote (Frontiers in Public Health, 2021)
Objectives: Study the prevalence and factors associated with the occurrence of surgical site infections in University Clinics of Trauma-Orthopedics, Reconstructive Surgery and Urology in a developing country. Methods: This was a retrospective descriptive and analytical study of 384 people operated on during the period of 2019. Logistic regression was used to study the factors associated with surgical site infections. The associations between the dependent variable and the other variables were assessed by the odds ratio (OR) followed by their 95% confidence interval. Results: The prevalence of surgical site infections was 7.81% CI95% = [5.12-10.51]. The factors linked to the surgical site infections in the studied population were the patient's admission method (OR = 2.74; 95%CI = [1.08 - 6.95]) and the length of the postoperative stay. (OR = 8.75; 95%CI = [2.83 - 26.98]). The interview and direct observation identified health care system dysfunctions, medical errors, patient monitoring and financial unavailability as factors that could favor the onset of surgical site infections. Conclusion: Interventions should be focused on the factors identified for the effective management of operated patients.